Fabrication of AgCl/Bi24O31Cl10 for Vis-Light Activated Photocatalytic Degradation of Tetracycline and Other Related Phenolic Organics in Aqueous Systems - Chirwa, Evans M.N. (University of Pretoria, 2023)
Thesis (PhD (Chemical Engineering))--University of Pretoria, 2023.